2018
DOI: 10.3390/f9110675
|View full text |Cite
|
Sign up to set email alerts
|

Bhutan’s Forests through the Framework of Ecosystem Services: Rapid Assessment in Three Forest Types

Abstract: Forests in mountain ecosystems provide a diversity of services and goods in mountain landscapes, and the immediate utility of the forest to upstream residents must be balanced with the insurance forests provide for downstream residents in the form of, especially, the services of water regulation and soil stabilization. Little empirical data exist for Bhutan that confirm a causal link between upstream forest use and downstream security. To help to fill this gap, we summarize the results of two literature review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…In line with other research in the region [14,42], our study confirms that community members understand and prioritize provisioning and cultural ecosystem services over regulating and supporting services. This is probably due to their historic and cultural interactions with these services for livelihood sustenance [15].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with other research in the region [14,42], our study confirms that community members understand and prioritize provisioning and cultural ecosystem services over regulating and supporting services. This is probably due to their historic and cultural interactions with these services for livelihood sustenance [15].…”
Section: Discussionsupporting
confidence: 90%
“…For example, it was reported elsewhere that regular environmental awareness programs were even more influential than the formal education levels in valuing the perceived importance of regulating services to the communities [63]. Given that residents of rural communities in the Himalayas are not highly educated, special consideration should be given to creating regular environmental awareness sessions focusing on all services, with emphasis on regulating and supporting services, so that communities can fully value the importance of their local forests [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one recent study, rapid assessment of community perception on the ecosystem services in Bhutan revealed that forests are seen as a source of rural livelihood with the highest ranking for provisioning services, including water, fuel wood, timber, fodder, and non-wood forest products [119]. On the other hand, supporting services like wildlife species and biodiversity in general received a low ranking in the order of importance indicating the need for community education and awareness on the importance of biodiversity conservation as the source of provisioning services.…”
Section: Performance Paymentsmentioning
confidence: 99%
“…In the world, forests play an important role in maintaining fundamental ecological processes, such as water regulation, carbon storage, the provision of livelihoods and support economic growth (de Groot et al, 2002;Holvoet and Muys, 2004;Gurung and Seeland, 2008;Thompson et al, 2011;Abson et al, 2014;Sears et al, 2018). However, nowadays, these forests are facing serious degradation resulting from important overexploitation, intensive agriculture, especially in developing countries (Lawson et al, 2014;Duguma et al, 2019).…”
Section: Introductionmentioning
confidence: 99%